RELATIONSHIP OF AEROBIC PERFORMANCE AND VENTILATION - Birgül Arslan; Tuba Melekoğlu (ümit doğan üstün, 2019)
Maximal oxygen consumption during exercise is an important determinant of aerobic capacity. Therefore, researchers use the aerobic tests evaluating maximal oxygen consumption (VO2max) to determine the aerobic capacity. VO2max depends on the capacity of the respiratory and circulatory systems to take up and distribute oxygen, and also the capacity of the muscles to receive and utilize it. Hence, there is three physiological systems affecting VO2max. In contrast to the circulatory and muscle systems, the respiratory system is usually not considered an important limiting factor for aerobic capacity because of its sufficient capacity to cope with the demands during high-intensity exercises. The aim of this research is to investigate the relationship between aerobic capacity and respiratory system parameters. Twenty healthy and trained males (24.3 ± 2.7 years, 178.1 ± 4.0 cm, 73.3 ± 7.1 kg) volunteered to participate in the study. The height, weight, body fat percentage, lean body mass, ventilation parameters, and maximal oxygen consumption were evaluated. After evaluating the distribution of the data, the Pearson Correlation Test was used to determine the relationship status. As a result of our study, a high correlation was found between VO2max and maximal ventilation volume (r=0.814; p=0.000), and a moderate correlation was found between VO2max and tidal volume (r=0.532; p=0.01). Even if the circulatory system was referred as the main factor affecting aerobic capacity in researches, the high correlation in our study results between VO2max and maximal ventilation volume shows that respiratory system should also be considered as an important factor for aerobic capacity.